Orofacial clefts in Brazil and surgical rehabilitation under the Brazilian National Health System - Giselle Firmino Torres de SOUSA; Angelo Giuseppe RONCALLI (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The objective of this study was to investigate the prevalence of live births with orofacial clefts in Brazil from 2009 to 2013, according to Brazil's federative units and regions, and correlate it with the number of corrective surgery procedures for cleft lip and palate performed through the Brazilian National Health System in the same period. The data were collected from the National Live Birth System (SINASC in Portuguese) and the Hospital Information System (SIH-SUS in Portuguese). The results showed that the average prevalence of oral clefts in the period was 5.86 per 10,000 live births, with differences observed between the federative units and the regions. The correlation between the prevalence of orofacial clefts and the number of medical procedures associated with this anomaly was statistically significant (r=0.94; p <0.001). This result indicates that greater investments are being made in areas with a higher number of cases. The relationship between supply and demand for corrective surgeries suggests that only 18.91% of the live births with orofacial clefts in this period may have received this service under the Brazilian National Health System.